Assessment of water, sanitation, and hygiene practices and associated factors in a Buruli ulcer endemic district in Benin (West Africa) - JOHNSON, ROCH CHRISTIAN; BONI, GRATIEN; Barogui, Yves Thierry; SOPOH, GHISLAIN E.; BOKO, MICHEL (My University, 2015)
Background: Control of neglected tropical diseases (NTDs) requires multiple strategic approaches including water, sanitation and hygiene services (WASH). Buruli ulcer (BU), one of the 17 NTDs, remains a public health issue in Benin particularly in the district of Lalo. The availability of water as well as good hygiene are important for the management of Buruli ulcer particularly in the area of wound care one of the main component of the treatment of BU lesions. Given the growing importance of WASH in controlling NTDs and in order to assess the baseline for future cross-cutting interventions, we report here on the first study evaluating the level of WASH and associated factors in Lalo, one of the most BU-endemic districts in Benin. Method: A cross-sectional study was carried to assess WASH practices and associated factors in the district of Lalo. Data were collected from 600 heads of household using structured pretested questionnaire and observations triangulated with qualitative information obtained from in-depth interviews of patients, care-givers and community members. Univariate and multivariate analysis were carried to determine the relationships between the potential associated factors and the sanitation as well as hygiene status. Results: BU is an important conditions in the district of Lalo with 917 new cases detected from 2006 to 2012. More than 49 % of the household surveyed used unimproved water sources for their daily needs. Only 8.7 % of the investigated household had improved sanitation facilities at home and 9.7 % had improved hygiene behavior. The type of housing as an indicator of the socioeconomic status, the permanent availability of soap and improved hygiene practices were identified as the main factors positively associated with improved sanitation status. Conclusions: In the district of Lalo in Benin, one of the most endemic for BU, the WASH indicators are very low. This study provides baseline informations for future cross-cutting interventions in this district.
Keywords: Benin; assessment of water; sanitation; endemic district